ANALYSE SOUS L’ANGLE ETHOLOGIQUE DES TENTATIVES DE SUICIDES CHEZ L’ADOLESCENT ABIDJANAIS - Kouame Atta (European Scientific Journal, ESJ, 2013)
This work is an ethological analysis of suicide-attempt which is observed in the behavior of Abidjan’s teenager. This phenomenon is becoming more and more common in urban African societies. The method used in this work is from social sciences because the analyzed behavior is complex (isolated feature and ethic) and can only be observed from strict methods of Ethology. It is based on the analysis of medical records of suicidal teenagers aged from 10 to 19 years. This survey was conducted through telephone communication. The obtained data were processed through statistics methods. The analysis has revealed that suicide-attempts have a universal aspect. This fact shows that suicide-attempts rest on a same biogenetic program which could be in relationship with “serotoninergic” factors of vulnerability and willing to commit suicide as revealed by many other writers’ works. At the phylogenetic level suicide-attempt is a specific behavior of mankind and at the “ontogenetic” level, it is seen in the behaviour of child since his childhood. This goes along with his biopsychic development. The results of different surveys conducted in this domain indicate that suicide-attempts observed in the behavior of Abidjan’s teenager are determined at the same time by factors linked to his biopsychics state and socio-affective factors linked to his family and his social environment. There is always a trigger event of suicide-attempt which can come from a disappointment, a failure or a family dispute.